1998
DOI: 10.1007/s11745-998-0202-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of n‐3 long‐chain polyunsaturated fatty acids with n‐6 fatty acids in suckled rat pups

Abstract: The addition of long-chain polyunsaturated fatty acids (LCP: C20, and C22) to infant formula may permit fatty acid accretion rates similar to breast-fed infants, and may have long-term outcome benefits, such as improved visual acuity and cognitive development. Although fish oil may provide a source of n-3 LCP, sources of n-6 LCP have been more difficult to identify. The present study evaluates the effects of n-3 and n-6 LCP derived from single-cell oils on liver, plasma, and brain fatty acid levels in a neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Five studies reported higher brain DHA in the low linoleic acid groups [31,32,35,37,39], whereas seven showed no effect of varying linoleic acid on brain DHA [33,34,36,38,[40][41][42]. The five studies that reported an effect all had dietary linoleic acid levels in the higher group of over 30% of fatty acids, whereas five of the seven showing no effect had dietary linoleic acid levels of less than 30% in the high group.…”
Section: Changes In Dietary Linoleic Acid and Effect On Brain Arachidmentioning
confidence: 95%
See 3 more Smart Citations
“…Five studies reported higher brain DHA in the low linoleic acid groups [31,32,35,37,39], whereas seven showed no effect of varying linoleic acid on brain DHA [33,34,36,38,[40][41][42]. The five studies that reported an effect all had dietary linoleic acid levels in the higher group of over 30% of fatty acids, whereas five of the seven showing no effect had dietary linoleic acid levels of less than 30% in the high group.…”
Section: Changes In Dietary Linoleic Acid and Effect On Brain Arachidmentioning
confidence: 95%
“…Twelve studies were identified that examined the effect of varying concentrations of dietary linoleic acid during early life on brain ARA and DHA [31][32][33][34][35][36][37][38][39][40][41][42]. Early life studies are here defined as those in which the dietary intervention began before weaning; in six studies dams were fed the diets throughout pregnancy [31][32][33][34][35][36], in two the dams were put on the diets in the second half of pregnancy [37,38], and in four, piglets were hand fed liquid diets from birth [39][40][41][42] (Table 1a).…”
Section: Changes In Dietary Linoleic Acid and Effect On Brain Arachidmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether the increased blood DHA and AA levels are reflected in tissues such as retina and brain is not known. For example, it has been reported that rats fed dietary AA supplements show significant increases in the plasma level of AA but not in the brain (14). Clearly, such issues can only be addressed easily with animal studies.…”
mentioning
confidence: 99%